Digital Health: The Cybersecurity for AI-Based Healthcare Communication - Abdullah M. Algarni; Vijey Thayananthan (IEEE Access)
The implementation of AI-based healthcare communication systems presents a significant challenge for the development of cost-effective medical environments. Despite numerous approaches introduced internationally, the field continues to grapple with real-world issues, demands, and a rising number of unforeseen diseases stemming from vulnerabilities, such as zero-day attacks. Purpose: The healthcare system, including communication between medical devices, must evolve alongside new technologies, such as AI-based proactive devices. Future healthcare hubs (future proactive devices), which will be deployed in various remote locations, utilize their own cybersecurity solutions to ensure secure AI-based healthcare communication services. Addressing these challenges requires managing potential issues arising in current medical scenarios. For instance, sudden security issues like ransomware attacks disrupting medical activities in London hospitals in May 2024 highlight the urgency of developing effective solutions that can be applied globally. Method: The AI-based approach offers a potential solution to these problems, although its implementation in medical security management presents challenges for the healthcare profession. While cybersecurity solutions are necessary, they can be developed through various management strategies. Anticipated Results: Implementing management solutions will require updating medical systems with AI-based policies. Efficient AI algorithms, derived from advanced mathematical or scientific techniques, are essential. The effectiveness of these solutions will ultimately determine the outcomes. Conclusion: Healthcare applications should be designed to be affordable while accommodating the essential facilities for human life.